THE EFFECT hCG (human Chorionic Gonadotropin) TO OVULATION AND HATCHING OF FISH EGG OF NILEM (Osteochilushasselti). - Aidil Irvan; Nuraini Nuraini; Indra Suharman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted from January to February 2018 in the halls 0f the fishery seeds Tarantang Subsdistrict, Harau, West Sumatra Province. The aims of this research was to know the effect ofhCG (Human Chorionic Gonadotropin) pituitary gland injected with different dose on ovulation and survivaln rate of nilem (Osteochilushasselti) and To find the best dose ot the pituitary gland to stimulate ovulation and survivaln rate of nilem (Osteochilushasselti). The treatment used is as follows : PO Control using NaCL 0,9 % as much 1 ml/kg weight of test fish. P1 : Injection of  hCG with dose 800 IU/kg weight of test fish. P2 : Injection of  hCG with dose 1000 IU/kg weight of test fish. P3 : Injection of hCG with dose 1200 IU/kg weight of test fish.The best result of the research is P3: Injection of hCG with dose 1200 IU/kg weight of test fish the with an average latent time 6 hours and 7minutes, amount eggs(items)/g 339 items,Fertilization Rate 60,82 % Hatching Rate 73,91 %, Survival Rate (SR7) 90,93 %Key word : Hormon hCG, Ovulation, Survival Rate, Osteochilus hasselti